الحصانة الجنائية للمبعوثين الدبلوماسيين بين ضرورة الوظيفة الدبلوماسية وخطورة الإفلات من العقاب - بدر, شنوف (University of Eloued جامعة الوادي, 2020)
لقد اعترفت اتفاقية فيينا للعلاقات الدبلوماسية للمبعوثين الدبلوماسيين بالحصانة القضائية الجنائية في الدول المعتمدين لديها، من أجل تأدية مهامهم فيها بكل حرية بعيداً عن كل المضايقات التي قد يتعرضون لها. بحيث تضمن لهم تلك الحصانة الإعفاء المطلق من الخضوع للقضاء الجنائي في تلك الدول، ما لم تتنازل دولهم عن تلك الحصانة. أما النظام الأساسي للمحكمة الجنائية الدولية فلم يعترف لهم بتلك الحصانة كعائق يمنع المحكمة من ملاحقتهم إذا ما ارتكبوا جرائم من اختصاصها. غير أن القبض عليهم وتسليمهم لها يبقى مرهوناً بتعاون الدولة التي يتواجدون فيها، وهم المتمتعون في مواجهتها بالحصانة القضائية بموجب اتفاقية فيينا، الأمر الذي قد يمنحهم فرصة للإفلات من العقاب . The Vienna Convention on Diplomatic Relations has recognized the diplomatic envoys with criminal judicial immunity in the countries in which they are accredited, in order to perform their duties in them freely, free from all the harassment to which they may be subjected. So that this immunity guarantees them absolute exemption from subject to criminal jurisdiction in those countries, unless their countries waive that immunity. As for the statute of the International Criminal Court, they did not recognize this immunity as an obstacle preventing the court from pursuing them if they committed crimes within its jurisdiction. However, their arrest and extradition remains subject to the cooperation of the state in which they are present, and they enjoy facing judicial immunity under the Vienna Convention, which may give them an opportunity to escape punishment.
مجلد11، عدد2
Keywords: المبعوثون الدبلوماسيون؛ الحصانة الجنائية؛ التنازل عن الحصانة؛ الجرائم الدولية، الإفلات من العقاب; : Diplomatic envoys; Criminal immunity; Waiver of immunity; International crimes; Impunity.